Formy oporu społecznego związanego z wyborami powszechnymi w Polsce w okresie „małej stabilizacji”– zarys problematyki - Danilecki, Tomasz (Pamięć i Sprawiedliwość, 2012)
Universal elections in the People’s Republic of Poland (PRL) were never free, therefore, they did not refl ect the true social attitude towards the system and individual governments; they only reaffi rmed the rulers’ political preferences in formal terms. They were a tool used to legitimise the system, perform a selection done by upper party authorities amongst the members of “upper bureaucratic class” and a peculiar survey to measure social support and the rulers’ ability to exert control over society. Social opposition to electoral incapacity was present with varying force through- out the period of PRL, even though historians were mentioning it sporadically and tritely, usually on margin of the descriptions of electoral campaigns that took place in times crucial for the nation, such as elections to the Legislative Parliament in 1947, or the fi rst parliamentary elections after the October turning point of 1956. Resistance to elections was proportionate to the restrictions of voting freedom imposed by the authorities, and the applied repressions. In the fi rst elections of the “Gomułka era” – in 1957 and 1958 – its relatively most frequent forms were open